Measuring indicators for marketing effectiveness in Czech companies - Frantisek Milichovsky (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
Marketing effectiveness has been accepted as one of the most important parts in corporate performance system. It is due to dynamical changes in business environment in after-crisis times. The goal of this paper is the denition of used possible indicators in measuring marketing effectiveness. The paper presents advance in usable indicators, especially financial and non-financial metrics. Selected studies, focusing on different branches and different indicators, were analysed by the author. The author of article puts the question, which classication is the most statistical explaining the difference of stakeholders in term of evaluation their impact on business management. There were made cluster analysis for data mining including its graphic presentation through dendogram and two-sample t-test by statistical software IBM SPSS Statistics 22 to obtain relevant answer on dened research question. Such limitation of the paper is possible to signify focusing only on domestic (Czech) industrial market.
Keywords: L21; L25; M21; M31; 330; marketing effectiveness; performance; financial indicators; non-financial indicators; engineering